Artificial intelligence-powered IoT-Based irrigation system for precision farming - Leao, Hen-Rin; Lee, Chu-Liang; Soon, Gregory How Thien; Lee, It-Ee; Chung, Gwo-Chin; Pang, Wai-Leong; Ng, Zi-Neng; Tan, Kar-Ban; Chan, Kah-Yoong (Elsevier, 2024)
Agriculture irrigation is an essential agricultural practice that ensures crops' healthy growth. Nonetheless, irrigation is labor-intensive and difficult to manage, particularly in large-scale farming operations. Smart irrigation systems are promising solution to the agricultural sector's challenges. These systems use sensors and other Internet of Things (IoT) technologies to monitor and control irrigation without much human intervention. Hence, several benefits are achievable, including lower labor costs, improved water efficiency, and increased crop yields. This study proposed a smart irrigation system using sensors to detect soil moisture levels and irrigate crops based on the detected moisture level. The proposed system also utilized a cloud-based platform to collect and store sensor data, which monitored the irrigation process and identified potential farming concerns. Besides, the system optimized the irrigation schedule to retain the soil moisture level from 80 to 90%. Therefore, the proposed smart irrigation system is a cost-effective and scalable solution that can improve irrigation efficiency in the agricultural sector.